Draft Annual Plan 1989-90 Part - I: Summary of Sectoral Outlay and Statistical Statements Union Territory of Daman and Diu - Planning Commission (Planning Commission, 1989)
'Daman & Diu’ are the two separate isolated land blocks situated at a distance of about 792 Kms. away from one another on the West coast of Arabian sea and on the border of Gujarat State. Both these pockets, formerly each comprising a dock cum district of erstwhile Union Territory of Goa, Daman and Diu have been formed into a separate Union Territory after de-linking of Goa, which attained a state hood on 30th May ’87. Earlier they were Portuguese colonies until 19th December, 1961 when they got liberated along with Goa.
Department of Planning and Statistics, Administration of Daman and Diu